Analisis Preferensi Industri Kecil Berbasis Tepung Terigu terhadap Pemilihan Jenis Tepung Terigu di Kotamadya Yogyakarta - Didi Adriansyah; Wahyu Supartono; Guntarti TM (agriTECH, 2000)
In the low class of small scale wheat flour based industries, price attribute played the most important role in choosing wheat flour, followed by dough rising, accessibility, dough elasticity, flavour and colour. The medium class wheat flour based industries had different considerations - price, dough elasticity, dough rising, flavour, accessibility and colour. The price attribute had still the first consideration in choosing wheat flour in the high class of small scale industries and than followed by accessibility, dough elasticity, dough rising, flavour and colour. This research also showed, that the most preferred wheat flour brand by small scale industries base in wheat flour were Cakra Kembang (50%), Segitiga Biru (43%), Beruang Biru (2,8%), Kunci Biru (1,4%), Melati (1,4%) and Raflesia (1,4%).